Distinctive mitogenomic lineages within populations of white-tailed eagles (Haliaeetus albicilla) ... - Hansen, Charles Christian Riis (Dryad, 2021)
Using whole mitochondrial DNA sequences from 89 white-tailed eagles (Haliaeetus albicilla) sampled from Iceland, Greenland, Norway, Denmark and Estonia between 1990-2018, we investigate the mitogenomic variation within and between countries. We show that there is a substantial population differentiation between the countries, reflecting similar major phylogeographic patterns obtained previously for the control region of the mitochondria, which suggested two main refugia during the last glacial period of Ice Age. Distinct mitogenomic lineages are observed within countries which divergence times exceeds the time since last glacial period of Ice Age ended. The lineages appear to have been maintained by natural selection. An excess of segregating amino acids in comparison with number of fixations, as revealed by the neutrality index suggests a load of deleterious mutations. The maintenance of mtDNA lineages within countries inflates our estimates of effective national population sizes and the times of their ... : Quality of the 89 individual fastq files was checked with FastQC, and then run through AdapterRemoval v2 to remove potential adapters when appropriate, using standard setting with the following customizing arguments: --collapse and --trimns. Individuals were mapped to the white-tailed eagle mitochondrial genome of a Korean specimen (NCBI: NC_040858.1) with bwa mem and converted to bam files using samtools view and sort. Bam files were transformed to vcf and fasta files using samtools mpileup with quality filters -q 30 and -Q 20, and bcftools call. The Korean reference sequence includes a NUMT in the 12s rRNA from position 492-538 (both included) which was removed from the alignment, resulting in total sequence length of 17,461 bp. Quality, depth, ratio of the common allele and binomial probabilities for all segregating sites were evaluated from the vcf file. A recently published mitochondrial genome of a German specimen (NCBI: MN356434.1) was retrieved from genebank and compared to our sequences. ...